Advances in the Preclinical Study of Some Flavonoids as Potential Antidepressant Agents. (1st February 2018) - German-Ponciano, León Jesús; Rosas-Sánchez, Gilberto Uriel; Rivadeneyra-Domínguez, Eduardo; Rodríguez-Landa, Juan Francisco
Abstract : Flavonoids are phenolic compounds found commonly in plants that protect them against the negative effects of environmental insults. These secondary metabolites have been widely studied in preclinical research because of their biological effects, particularly as antioxidant agents. Diverse flavonoids have been studied to explore their potential therapeutic effects in the treatment of disorders of the central nervous system, including anxiety and depression. The present review discusses advances in the study of some flavonoids as potential antidepressant agents. We describe their behavioral, physiological, and neurochemical effects and the apparent mechanism of action of their preclinical antidepressant-like effects. Natural flavonoids produce antidepressant-like effects in validated behavioral models of depression. The mechanism of action of these effects includes the activation of serotonergic, dopaminergic, noradrenergic, and γ -aminobutyric acid-ergic neurotransmitter systems and an increase in the production of neural factors, including brain-derived neurotrophic factor and nerve growth factor. Additionally, alterations in the function of tropomyosin receptor kinase B and activity of the enzyme monoamine oxidase A have been reported. In conclusion, preclinical research supports the potential antidepressant effects of some natural flavonoids, which opens new possibilities of evaluating these substances to develop complementary therapeutic alternatives that could ameliorate symptoms of depressive disorders in humans.